CAR T-cells and macrophages in large B-cell lymphoma: impact on toxicity and efficacy. Issue 4 (21st March 2023) - Al Zaki, Ajlan; McCurry, Dustin; Strati, Paolo
Abstract: Chimeric antigen receptor (CAR) T-cell therapy targeting CD19 is the current standard of care for the treatment of relapsed refractory large B cell lymphoma, demonstrating impressive response rates in the second- and third-line setting. Despite these advances, this treatment strategy can result in significant toxicities, such as cytokine release syndrome or immune effector cell associated neurotoxicity syndrome. While the exact mechanisms of these immune-mediated toxicities are not clearly understood, emerging pre-clinical and clinical studies have revealed the pivotal role of myeloid cells, particularly macrophages, as key contributors to the efficacy of treatments and as crucial mediators of toxicity. In this review, we discuss the current understanding of how macrophages mediate these effects, highlighting specific mechanisms of macrophage biology relevant to CAR T-cell therapy activity and side effects. These findings are resulting in novel treatment strategies that target macrophages, and able to mitigate toxicity while preserving CAR T-cell therapy efficacy.